Medieval Texts and Contemporary Readers - Finke, Laurie A. (Cornell University Press, 2019)
This collection brings together twelve original essays by prominent medievalists which address problems posed by contemporary literary and cultural theory. Taken together, the essays call into question the view that contemporary criticism has little to say about medieval literature and that medieval studies should remain isolated from the issues of contemporary criticism. The contributors apply a variety of critical methodologies to explore issues in textuality, intertextuality, and the role of the reader in works of medieval writers as diverse as Chaucer, Dante, Christine de Pizan, Anselm, and Talavera. Incorporating critical approaches such as deconstructionism, Marxism, feminism, new-historicism and reader-response criticism, the essays place these writers and their texts within a wider realm of cultural reference that embraces philosophy, religion, rhetoric, history, politics, and anthropology.